Failure of Dental Implants and its Association with IL-10 A/G rs1800896 and TNF-α G308A rs1800629308 Polymorphisms, Systematic Review, and Meta-Analysis of Clinical Trials - Bono, Alejandra (2025)
Fil: Bono, Alejandra, Liliana. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de patología oral; Argentina.